KONTESTASI DAN ADAPTASI OTORITAS KEAGAMAAN TRADISIONAL: MENCERMATI VISI DAKWAH PESANTREN DARUL FALAH BANGSRI JEPARA - Shiyamil Awaliah; Masduki Masduki (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
This article discusses about traditional religion that continues to develop in the midst of modern technological and informative life. However, this development does not mean attaching religious authority to its thick local cultural culture. Kyai Taufiqul Hakim is one of example from figure who managed to maintain traditional authority. Amtsilati, the yellow book learning method in the Darul Falah boarding school, is a learning media used to maintain that authority. What was revealed from the contestation was the vision of his da'wah which was a stimulation to remain and consistently study the yellow book. Through a descriptive method and accessing normative juridical data collected through library studies are analyzed and conclusions are then taken. This article explains that Kyai Taufiqul Hakim successfully passed his missionary vision of preserving Islamic boarding school culture by bring out the Islamic scientists who still discussed the religion of Islam using the amtsilati method. This indicates that traditional Islamic authority as exemplified by the Darul Falah boarding school is able to contest and adapt to modern developments.